Developing reading comprehension skills among the educable mentally retarded in the intermediate level - Tablang, Victoria Reyes 1942-; Sison, Waldetrudes Montojo (1972)
This paper focused on the comprehension skills that can be developed among the educable mentally retarded in the intermediate level. The aim of the study was to provide teachers of the educable mentally retarded a guide for the development of reading comprehension skills among the special children. Library research was used in gathering data for this study.
"April, 1972."
Vita.
Thesis (Master of Arts in Teaching - Special Education)--University of the Philippines, Diliman.
Keywords: Reading comprehension -- Philippines; Children with mental disabilities -- Education (Elementary) -- Philippines; Reading (Elementary) -- Activity programs -- Philippines